Community leadership, policy implementation and rural revitalization in China: perspectives for Africa - Joshua Mugambwa; Tang Lixia; Xu Xiuli (Cogent Social Sciences)
Rural poverty remains a major challenge in developing countries, hindering quality of life, reducing life expectancy and stalling development. Despite Africa’s rich resources, including a favorable climate and fertile soil, it still relies on food imports, highlighting the need for rural transformation. In contrast, China successfully eradicated extreme poverty in 2020 through a strategic rural revitalization plan. This study examines the relationship between community leadership, policy implementation and rural revitalization in China to draw lessons for Africa. Specifically, it explores the role of community leadership in policy execution and rural revitalization and identifies applicable insights for Africa. A case study design was used, with qualitative data collected from 15 key informants in Youyang Tujia County and Miao Autonomous County, Chongqing Municipality. Findings indicate that China’s success in rural revitalization is driven by strong community leadership that effectively implements policies. This leadership fosters active participation, embraces research and technology and prioritizes infrastructure investment. Key lessons for Africa include the need for strong political will, zero tolerance for corruption, inclusive institutions and a bottom-up approach that engages citizens. These findings are relevant to policymakers, development practitioners and researchers in rural development. Comprehensive policies should leverage community cooperation, technology and grassroots participation for effective rural transformation in Africa.